2009
DOI: 10.1038/gt.2009.128
|View full text |Cite
|
Sign up to set email alerts
|

Targeting human glioma cells using HSV-1 amplicon peptide display vector

Abstract: Targeting cell infection using herpes simplex virus type 1 (HSV-1) vectors is a complicated issue as the process involves multiple interactions of viral envelope glycoproteins and cellular host surface proteins. In this study, we have inserted a human glioma-specific peptide sequence (denoted as MG11) into a peptide display HSV-1 amplicon vector replacing the heparan sulfate-binding domain of glycoprotein C (gC). The modified MG11:gC envelope recombinant vectors were subsequently packaged into virions in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…reported that HSV-1 was retargeted to a specific receptor IL13Rα2 expressed in malignant glioma, by ablating the HS-binding sites of gB and gC, and the insertion of IL-13 in the N-terminal of gC and gD, but the recombinant virus can still infect normal cells by interaction with HVEM or nectin 1 (Zhou et al., 2002 ). The glycoprotein gC can also be retargeted to the human glioma cells through the ligand human glioma-specific peptide sequence (denoted as MG11) (Ho et al., 2010 ).…”
Section: Tumor Targeting Of Ohsvs By Engineering Their Envelope Glycomentioning
confidence: 99%
“…reported that HSV-1 was retargeted to a specific receptor IL13Rα2 expressed in malignant glioma, by ablating the HS-binding sites of gB and gC, and the insertion of IL-13 in the N-terminal of gC and gD, but the recombinant virus can still infect normal cells by interaction with HVEM or nectin 1 (Zhou et al., 2002 ). The glycoprotein gC can also be retargeted to the human glioma cells through the ligand human glioma-specific peptide sequence (denoted as MG11) (Ho et al., 2010 ).…”
Section: Tumor Targeting Of Ohsvs By Engineering Their Envelope Glycomentioning
confidence: 99%